The influence of pavement degradation on population exposure to road traffic noise - Freitas, E. F. (2019)
Road pavement develops distresses over time, which increase tyre/road noise. This work focuses on the impact of these distresses on environmental noise. To calculate the environmental noise, a method to transform Close ProXimity (CPX) measurement results into the required input for traffic noise models was defined and used. The tyre/road noise levels were determined by the CPX method for three types of pavement, with three types of distress, at three different speed levels. The study was carried out in the city center of Guimarães, a medium-sized Portuguese city. Using the NMPB model, 18 noise maps were produced for the passing of one single vehicle, taking into account two levels of distress (50% and 100%) for the pavement. The presence of distresses increased the noise, calculated at control points, by up to 7.1 dBA, and the percentage of the population exposed to levels over 45 dB was more than 11%. It was shown that pavement maintenance at early stages of distress development is, particularly for low-speed roads, very important to reduce environmental noise and population exposure. A comprehensive selection of the type of surface and speed control policies can mitigate the impact of a lack of maintenance.